Management Of Pseudoaneurysm In A Single Surgeon Vascular Unit in East Coast Malaysia - Dev, Sanjay; Salmi, Irfan; Othman, Faidzal; Jaafar, Muhammad; Mohamed, Malek (2021)
Introduction Pseudoaneurysm, also known as false aneurysm, occurs when there is a localised extravasation of blood from the arterial wall and is confined by a pseudocapsule. There is an increasing trend in cases of iatrogenic pseudoaneurysms due to the increase rates of endovascular procedures. Open surgical repair used to be the mainstay of treatment, however it has since been replaced by less invasive approaches such as ultrasound-guided compression and endovascular techniques such as stenting and embolization.